2001
DOI: 10.1038/sj.onc.1204630
|View full text |Cite
|
Sign up to set email alerts
|

p53 directs conformational change and translation initiation blockade of human fibroblast growth factor 2 mRNA

Abstract: Tumour suppressor p53 has been shown to inhibit ®broblast growth factor 2 expression post-transcriptionally in cultured cells. Here we have investigated the mechanism responsible for this post-transcriptional blockade. Deletion mutagenesis of the FGF-2 mRNA leader revealed the requirement of at least four RNA cisacting elements to mediate the inhibitory e ect of p53 in SK-Hep-1 transfected cells, suggesting the involvement of RNA secondary or tertiary structures. Recombinant wild-type, but not Ala 143 mutant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
0
41
2
Order By: Relevance
“…Within the FGF family, p53 has been shown to inhibit fgf2 gene expression at the transcriptional level, but the fgf2 promoter does not contain either a typical TATA box or a p53-DNA-binding consensus sequence (Ueba et al, 1994). It has also been reported that p53 inhibits fgf2 expression at posttranscriptional levels, by blocking the initiation of translation of human fgf2 mRNA (Galy et al, 2001a, b). fgf1 expression is mainly regulated at the transcriptional level: different promoters, alternative splicing and multiple polyadenylation signals generate different fgf1 transcripts (Crumley et al, 1989;Philippe et al, 1992Philippe et al, , 1996Renaud et al, 1992;Chiu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Within the FGF family, p53 has been shown to inhibit fgf2 gene expression at the transcriptional level, but the fgf2 promoter does not contain either a typical TATA box or a p53-DNA-binding consensus sequence (Ueba et al, 1994). It has also been reported that p53 inhibits fgf2 expression at posttranscriptional levels, by blocking the initiation of translation of human fgf2 mRNA (Galy et al, 2001a, b). fgf1 expression is mainly regulated at the transcriptional level: different promoters, alternative splicing and multiple polyadenylation signals generate different fgf1 transcripts (Crumley et al, 1989;Philippe et al, 1992Philippe et al, , 1996Renaud et al, 1992;Chiu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While viral IRESes participate in a mechanism aimed at the misappropriation of the cellular translational machinery from cellular mRNAs, cellular IRESes allow the expression of certain mRNAs in conditions in which cap-dependent translation initiation is severely impaired. RNA conformation is thought to be critical for the activity of several viral and cellular IRESes (Kaminski et al, 1990;Galy et al, 2001;Mitchell et al, 2003). Here, we show that c-myc P2 mRNA 5 0 UTR is predicted to fold in a Y-shaped secondary structure characteristic of viral IRESes (Le et al, 1996) (Figure 1).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, c-myc IRES activity is observed in apoptotic cells, during the G2/M transition of the cell cycle and upon genotoxic stress, conditions in which cap-dependent translation is severely impaired (Pyronnet et al, 2000;Stoneley et al, 2000;Subkhankulova et al, 2001). In vivo, the c-myc IRES is mainly active during embryogenesis, and is downregulated at later stages of development (Cre´ancier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, p53, which is able to inhibit the FGF-2 IRES activity, also acts by modifying the RNA structure. 33 Thus, we can hypothesize that ITAFs may also act on mRNA stability: if the mRNA is highly structured, it may presumably render it more resistant to RNAses. p53 is probably not responsible for the FGF-1 IRES inhibition in 911 cells, as these cells express the adenovirus E1 protein that complexes and inactivates p53.…”
Section: Aav-derived Bicistronic Vector With the Fgf-1 Ires A Delluc-mentioning
confidence: 99%